SOCIAL PROBLEMS AND ENVIRONMENT: सामाजिक समस्याएँ व पर्यावरण - Jadhav, B.S. (International Journal of Research -GRANTHAALAYAH, 2015)
From time immemorial modern man has set many measures of progress and progress. Man has progressed along with the development of intelligence. Human has developed his own nature by exploiting nature's qualities, but in this dark sense of development, human nature has contributed to the environment, to give up nature, to damage its environment. In which natural disorganization is associated with this disease. This imbalance has caused serious problems to human beings. आदिमकाल से लेकरवर्तमानआधुनिक युगतकमनुष्य ने उन्नति व प्रगतिव के अनेकसोपान तय किए है।मनुष्य ने बुद्धि के विकास के साथ-साथप्रगति की है।मानव ने प्रकृतिप्रदत्तसाधनोंकादोहनकरअपनाविकासकियाहै, किन्तुविकास की इसअन्धीदौड़ मेंमनुष्य ने प्रकृतिप्रदत्तसंसाधनोंकाअविवेकपुर्णदोहन ने प्रकृति व पर्यावरणकोअत्यंत क्षतिपहुचाॅईहै।मनुष्य की निरन्तर बढ़तीआवश्यकताओं ने पर्यावरणको क्षतिपहुचाईहै, जिसमेेंप्राकृतिकअसुतंलनकोजन्मदिया।इसअसंतुलन ने मानव के समक्ष गंभीरसंकटउत्पन्नकरदिए है